Advancing Error-Correcting Codes through the Application of Algebraic Curves in Coding Theory - Al-Zuriqat, Mai Hathal; Obeidat, Bushra (Journal of Research in Vocational Education, 2025)
This study investigates the intersection of algebraic geometry and coding theory, specifically focusing on the application of algebraic curves in the advancement of error-correcting codes. Algebraic curves, as mathematical objects, offer profound implications in the design and analysis of error-correcting codes, providing robust solutions to the challengesof data transmission and storage. This paper delves into the theoretical foundations ofalgebraic curves, their role in constructing powerful error-correcting codes, and the practicalapplications of these codes in various technological domains.